Analysis of CEO Characteristics (Gender), CEO Age, and Tenure on Corporate Debt Policy - Latif, Abdul; Afandi, Dian Rachmawati; Hidayah, Zulfa Zakiatul; Apriani, Erna (Journal of Business and Behavioural Entrepreneurship, 2024)
Debt policy is one of the most important factors for companies that have gone public or not in maintaining the image of existing information to investors. As well as being one of the references for investors in deciding their investment actions. Thus, as an academic practitioner and also a capital market investor, this research theme is a topic of urgency in the perspective of the CEO (Gender) to be raised. The specific purpose of this study is to analyse the differences in debt policy among energy sector companies listed on the Indonesia Stock Exchange, with a focus on the character of the CEO (Gender), the age of the CEO, and the tenure of the CEO of the corporation. The research data analysis technique uses an independent mean difference test to test the hypothesis in this study, the first thing to do first is the assumption test or the feasibility of the research data model. The results showed the first that there was no significant difference in the Company led by Female CEO and male CEO, the second result showed that there was no significant difference in the Company led by CEO less than 45 years old and CEO more than 45 years old, the third result showed that there was no significant difference in the Company led by CEO with tenure below 10 years and the Company led by CEO with tenure above 10 years on corporate debt policy.